FC 087MIR-155/SOCS1 REGULATORY LOOP INFLUENCES DIABETIC KIDNEY DISEASE BY JAK/STAT PATHWAY MODULATION. (29th May 2021) - Prieto, Ignacio; Jimenez-Castilla, Luna; Lazaro, Iolanda; Bernal-Uribe, Susana; Lopez-Sanz, Laura; Flores-Muñoz, Mónica; Egido, Jesus; Lopez-Franco, Óscar; Gomez-Guerrero, Carmen
Abstract: Background and Aims: Diabetic nephropathy is the leading cause of chronic kidney disease worldwide. Hyperglycemia in concert with cytokines activate Janus kinase/signal transducers and activators of transcription (JAK/STAT) signaling pathway and induce gene expression of many inflammatory and oxidative stress mediators, which are critical events at all stages of diabetic kidney disease. Suppressor of cytokine signaling 1 (SOCS1) is a STAT-inducible protein and a negative feedback regulator of JAK/STAT pathway. The microRNA-155 is an epigenetic modulator of SOCS1 gene by repressing its translation and, at the same time, is a transcriptional target of STAT, thus completing another regulatory loop of JAK/STAT pathway. Therefore, our aim was to explore the interplay between miR-155 and JAK/STAT/SOCS1 axis in experimental diabetic nephropathy. Method: In streptozotocin-induced type 1 diabetic aged mice (wild-type and apolipoprotein E (apoE) knockout) we analyzed the kidney levels of miR-155 and markers of renal damage, inflammation and oxidative stress. In vitro, the expression of miR-155, SOCS1 and STAT1 in mesangial, tubuloepithelial and macrophage cell lines were modulated by silencing/inhibition or overexpression/mimicking experiments to further determine the JAK/STAT pathway activation and expression of downstream target genes. Results: In vivo, type 1 diabetes significantly upregulated miR-155 expression in kidneys from both wild-type and apoE knockout mice (1.8- and 4.5-fold vs respective non-diabetic controls). The miR-155 levels directly correlated with parameters of renal damage (serum creatinine, albuminuria, kidney-to-body weight ratio and renal score) and the mRNA expression of chemokines (Ccl2 and Ccl5) and pro-oxidant enzymes (Nox2 and Nox4), but inversely with antioxidant genes (Sod1 and Cat). In vitro, the expression of miR-155 was increased in renal cells and macrophages exposed to hyperglycemia and/or inflammatory conditions. Overexpression of miR-155 reduced SOCS1 expression, enhanced STAT1 and STAT3 activation and pro-inflammatory cytokines and chemokines (Il6, Tnfa, Ccl2 and Cxcl10) expression. By contrast, miR-155 antagonist upregulated SOCS1 and had a protective effect on renal cells by decreasing STAT1/3 phosphorylation and pro-inflammatory gene expression. Additionally, loss- or gain-of function experiments indicate a direct implication of SOCS1 in the regulation of miR-155 expression by STAT transcription factors. Conclusion: Our study indicates a pro-inflammatory role of miR-155 in diabetic kidney disease by downregulating renal expression of SOCS1. Therefore, antagonism of miR-155 may have a renoprotective effect in diabetic nephropathy through SOCS1-mediated feedback inhibition of JAK/STAT overactivation. Ongoing in vivo studies with miR-155 inhibitor in experimental diabetes will clarify its role in the development and progression of diabetic nephropathy.